Peran Demosi dalam Meningkatkan Profesionalisme Kinerja Pendidik dan Tenaga Kependidikan - Rumi, Achmad Jalaludin; Kencana, Masayu Rindang Bayu; Kamila, Shafira Azzah (TSAQOFAH, 2024)
Demotion is a decrease in the position of an employee that occurs because the employee does not meet the requirements in carrying out the responsibilities of the assigned duties and violates a serious code of ethics. This research was conducted with the aim of knowing how the role of demotion in improving performance professionalism for educators and education personnel. The research method used is a qualitative method, by conducting an interview with one of the teachers at SMA Negeri 20 Surabaya. Based on the results of the interview, it was found that there is no demotion in public schools, as well as SMA Negeri 20 Surabaya, but private schools have the possibility of demotion by reducing one's position from GTY (Permanent Foundation Teacher / Permanent Foundation Employee) to GTT (Non-Permanent Teacher / Non-Permanent Employee). MGMP and certification are things that can be done to avoid demotion. The conclusion of this article is that demotions do not exist in public schools but may exist in private schools and to avoid demotions, cooperation between employees, teachers and schools is needed to improve the quality of performance.